2009
DOI: 10.1097/sla.0b013e3181a40919
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors For Ipsilateral or Contralateral Central Lymph Node Metastasis in Unilateral Papillary Thyroid Carcinoma

Abstract: Unilateral PTC with a maximal diameter of greater than 1 cm is associated with a high rate of ipsilateral central neck LN metastasis. Moreover, ipsilateral central LN metastasis is a potential independent predictor of synchronous contralateral central LN metastasis. These findings suggest that contralateral as well as ipsilateral elective CLND, performed during the initial thyroid operation, may be effective in the management of patients with unilateral PTC having a maximal diameter of greater than 1 cm and ip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
117
4
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(135 citation statements)
references
References 24 publications
11
117
4
3
Order By: Relevance
“…The male gender has been consistently recognized as an independent risk factor of lymph node metastasis in thyroid carcinoma (14). Females are comparatively prone to thyroid Table III.…”
Section: Discussionmentioning
confidence: 99%
“…The male gender has been consistently recognized as an independent risk factor of lymph node metastasis in thyroid carcinoma (14). Females are comparatively prone to thyroid Table III.…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent meta-analysis has found that those with clinically nodal negative (cN0) neck who undergo pCND might have reduced risk of LR than those who undergo TT-alone in the short-term, the former group has higher risks for temporary hypoparathyroidism and overall morbidity . Therefore, identification of predictive factors for occult CNM is crucial to reduce unnecessary pCND (Koo et al 2009, Hartl et al 2012, Zhang et al 2012, Zhao et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The fact is that some 30-60% of clinically negative central necks will harbour metastatic lymph nodes (10,27,30). Some authors do not consider subclinical lymph node involvement as a risk factor for recurrence, because usually metastatic nodes are few in number and will be sterilized by routine radioidine ablation (37).…”
Section: Prophylactic Central Neck Dissectionmentioning
confidence: 99%
“…In some 5-10% of cases, N1b disease (lateral lymph node metastasis) may skip the central neck, usually in cases where the tumour is located in the upper poles of the thyroid (29). The most widely recognized pathological variable associated with central neck metastasis in advanced PTC is extrathyroidal invasion usually, but not always, associated with large tumours (28,30,31).…”
Section: How Often Is the Central Neck Compartment Involved In Non-mimentioning
confidence: 99%